Unlocking the Therapeutic Potential of Ellagic Acid for Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis - Tharani Senavirathna; Armaghan Shafaei; Ricky Lareu; Lois Balmer (MDPI AG, 2024)
Obesity is in epidemic proportions in many parts of the world, contributing to increasing rates of non-alcoholic fatty liver disease (NAFLD). NAFLD represents a range of conditions from the initial stage of fatty liver to non-alcoholic steatohepatitis (NASH), which can progress to severe fibrosis, through to hepatocellular carcinoma. There currently exists no treatment for the long-term management of NAFLD/NASH, however, dietary interventions have been investigated for the treatment of NASH, including several polyphenolic compounds. Ellagic acid is one such polyphenolic compound. Nutraceutical food abundant in ellagic acid undergoes initial hydrolysis to free ellagic acid within the stomach and small intestine. The proposed mechanism of action of ellagic acid extends beyond its initial therapeutic potential, as it is further broken down by the gut microbiome into urolithin. Both ellagic acid and urolithin have been found to alleviate oxidative stress, inflammation, and fibrosis, which are associated with NAFLD/NASH. While progress has been made in understanding the pharmacological and biological activity of ellagic acid and its involvement in NAFLD/NASH, it has yet to be fully elucidated. Thus, the aim of this review is to summarise the currently available literature elucidating the therapeutic potential of ellagic acid and its microbial-derived metabolite urolithin in NAFLD/NASH.